THE MAIN CHARACTER’S RESPONSE TO RACIAL DISCRIMINATION IN INVICTUS MOVIE - Yahya, Muhamad Fikri; Al-Baroroh, Aisyah (Linguistics and Literature Journal, 2025)
This article examines how the main character, Nelson Mandela, responds to racial discrimination in Invictus (2009), directed by Clint Eastwood. The research focuses on Mandela’s strategies in addressing the deep racial divisions in post-apartheid South Africa. Using John Paul Lederach’s theory of reconciliation, the analysis highlights four key responses shown by Mandela: truth, forgiveness, justice, and peace. These responses are expressed through dialogue, symbolic actions, and leadership decisions in the film. The findings reveal that Mandela’s commitment to reconciliation helped transform rugby, a sport once seen as a symbol of racial division, into a unifying tool for the nation. His responses demonstrate that racial discrimination can be resisted not only through political struggle but also through moral leadership and inclusive vision. This article aims to give readers a deeper understanding of how film portrays responses to racial discrimination and to provide a useful reference for further studies in literature and film analysis. Keywords: film analysis, Invictus, Nelson Mandela, racial discrimination, reconciliation